The Indonesia Public Information Disclosure Act (UU-KIP): Its Challenges and Responses - Muharman Lubis; Tien Fabrianti Kusumasari; Lukmanul Hakim (Institute of Advanced Engineering and Science, 2018)
Information Public Disclosure is one of the regulation that has purpose to encourage good governance for public service and citizen participation in national development. The enactment of Act No.14/2008 (UU KIP) has been strengthen the mandate to enforce the necessity of information disclosure in actualizing transparency and accountability in resource management and budget uses. It also become the primary instrument to prevent corruption, monopolistic competition and information disputes. However, there are certain provinces has not yet established information committee nor when it will be as entrusted by the regulation. Meanwhile, the remedies in term of jail duration and fines, arguably, it could not create deterrent effect to the perpetrator. Furthermore, the concern from ministry and public institution also in question in regard their roles of responsibility, lack of cooperation and continuous support. Thus, human resource, technology infrastructure, public participation, supervision and socialization become crucial factor to increase the awareness and satisfaction towards this regulatory compliance. This study is a qualitative research to evaluate the implementation of this Act by observing its consideration, background, principles and relevant article verses as primary sources through content analysis based on number of legal experts.